2000
DOI: 10.1074/jbc.m003559200
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-dependent Differences in Thyroid Peroxidase Cell Surface Expression

Abstract: Recently, it has been suggested that only ϳ2% of human thyroid peroxidase (hTPO 933 ) reaches the surface of stably transfected (Chinese hamster ovary) cells, most being degraded intracellularly, and this might be representative of thyroid peroxidase (TPO) behavior in thyrocytes (Fayadat, L., Siffroi-Fernandez, S., Lanet, J., and Franc, J.-L. (2000) In the past decade, cell type-dependent differences in membrane and secretory protein trafficking have been increasingly recognized. Certainly, the rate and effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…In primary porcine thyrocytes after 7 days in culture, ϳ30% of endogenously expressed TPO could be biotinylated at the cell surface (40), and a similar number has been reported for recombinant hTPO (41). Another study proposed that only 2% of cellular TPO may reside at the plasmalemma (26), but there are reasons to wonder if all of these studies might represent great underestimates of the TPO surface distribution (both because of intracellular lumina that may sequester plasmalemmal proteins during thyrocyte primary culture (25) and because of low biotinylation efficiency of surface TPO (27)). Alternatively, some investigators have examined acquisition of endo H resistance to estimate the fraction of cellular TPO molecules that have proceeded beyond the ER through the secretory pathway, and this fraction is very low in real thyroid tissue (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In primary porcine thyrocytes after 7 days in culture, ϳ30% of endogenously expressed TPO could be biotinylated at the cell surface (40), and a similar number has been reported for recombinant hTPO (41). Another study proposed that only 2% of cellular TPO may reside at the plasmalemma (26), but there are reasons to wonder if all of these studies might represent great underestimates of the TPO surface distribution (both because of intracellular lumina that may sequester plasmalemmal proteins during thyrocyte primary culture (25) and because of low biotinylation efficiency of surface TPO (27)). Alternatively, some investigators have examined acquisition of endo H resistance to estimate the fraction of cellular TPO molecules that have proceeded beyond the ER through the secretory pathway, and this fraction is very low in real thyroid tissue (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have previously reported that recombinant TPO expression, even in clones derived from single cells, results in two cell subpopulations, each of which maintain comparable total TPO protein expression but only one of which maintains surface TPO protein expression (27). Therefore, we bathed live 293-22 cells expressing rTPO in medium containing anti-rTPO and a fluorescent-conjugated anti-rabbit secondary antibody and used flow cytometry and fluorescence-activated cell sorting (FACS) to segregate the cells into FACS-negative and FACS-positive subpopulations (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Newly synthesized TPO is transported from the endoplasmic reticulum to the cell surface via the Golgi complex (20,(22)(23)(24). During processing and intracellular trafficking TPO interacts with the molecular chaperones calnexin, calreticulin (25), and BiP (26).…”
Section: Introductionmentioning
confidence: 99%